EIB Working Paper 2021/08 - Do capacity constraints trigger high growth for enterprises? - European Investment Bank (European Investment Bank, 2021)
High-Growth Enterprises have a large economic impact, but it is notoriously hard to predict when firms will experience episodes of high growth. This paper proposes that firms reaching critically high capacity utilisation levels reach a 'trigger point' involving either broad-based investment in further growth, or shrinking back to previous levels. It analyses EIBIS survey data (matched to the ORBIS database) which features a question on time-varying capacity utilisation. Overcapacity is a transitory state. Firms enter into overcapacity after a period of rapid growth of sales and profits, and the years surrounding overcapacity have higher employment growth rates. Firms operating at overcapacity make incremental investments (e.g. capacity expansion, process improvements, and modern machinery) rather than investing in R&D and new product development. The analysis finds support for the 'fork in the road' hypothesis: for some firms, overcapacity is associated with launching into massive investments and subsequent sales growth, while for other firms, overcapacity is negatively related to both investments and sales growth.